2018
DOI: 10.2147/ijn.s156206
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethyl chitosan nanoparticles loaded with bioactive peptide OH-CATH30 benefit nonscar wound healing

Abstract: BackgroundNonscar wound healing is a desirable treatment for cutaneous wounds worldwide. Peptide OH-CATH30 (OH30) from king cobra can selectively regulate the innate immunity and create an anti-inflammatory micro-environment which might benefit nonscar wound healing.PurposeTo overcome the enzymatic digestion and control release of OH30, OH30 encapsulated in carboxymethyl chitosan nanoparticles (CMCS-OH30 NP) were prepared and their effects on wound healing were evaluated.MethodsCMCS-OH30 NP were prepared by mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…Cathelicidin-carboxymethyl chitosan nanoparticles only enhanced cell migration, without influencing keratinocyte growth. Moreover, in later stages of wound closure, the ratio of collagens I and III favored non-scaring healing [46].…”
Section: Nanomaterials In Wound Healingmentioning
confidence: 99%
“…Cathelicidin-carboxymethyl chitosan nanoparticles only enhanced cell migration, without influencing keratinocyte growth. Moreover, in later stages of wound closure, the ratio of collagens I and III favored non-scaring healing [46].…”
Section: Nanomaterials In Wound Healingmentioning
confidence: 99%
“…In this study, CMC-ClyR-ACP nanogel was successfully synthesized. We speculate that, since CMC is negatively charged (pI~5.14) and ClyR is positively charged (pI~8, as predicted by online software Expasy) at pH 7.4, it is likely for these two compounds to bind to each other mainly by electrostatic interactions coupled with hydrogen bonding and van der Waals forces, as other studies have shown [29,35]. In the CMC-ClyR-ACP nanogel, CMC could still maintain calcium and phosphorus at an amorphous state.…”
Section: Discussionmentioning
confidence: 74%
“…Chitosan nanoparticles were considered as an effective delivery system of the vaccine due to the advantages of biocompatible, biodegradable, mucoadhesive, polycationic, and immunomodulatory properties 36,37. In this study, we explored the effectiveness of CNPs as an immune adjuvant and vaccine delivery system by adsorbing the recombinant Ags on CNPs.…”
Section: Discussionmentioning
confidence: 99%